Entrepreneurship shaping the business environment in rural areas evaluation of the service of subjects (Texas Journal of Multidisciplinary Studies, 2023)
The article analyzes the organizational and economic mechanisms of the development of small business and private entrepreneurship in rural areas, and gives conclusions and recommendations